Sustainable energy management for ports - Ko, Ming Jun (2016)
Major energy consumers such as sea ports are subjected to increased scrutiny from regulatory bodies and the public in recent years. In response, sea ports around the globe have been progressively adopting green practices in port operations ranging from using energy-efficient equipment to green energy production. This article proposes the idea of Energy Management System (EnMS) implementation to better manage energy within a sea port. EnMS is further discussed with discrete event simulation to model after energy flow in a sea-port and cost-benefit analysis.